THE CREATION OF A CINEMA WORLD AS A FICTIONAL PROCESS (ON THE MATERIAL OF FILMS OF UKRAINIAN “POETIC CINEMA”) - Khorob, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article considers some aspects of a creative process over the film. On the example of motion pictures of the representatives of the Ukrainian “poetic cinema”, as well as of the creative work of their producers the attempt is made to single out peculiarities of psychology of creative work, its phases and stages. It is proved that such movies as “Tini zabutykh predkiv”, “Propala hramota”, “Vechir na Ivana Kupala”, “Kaminnyi khrest”, “Vavylon XX” and their creators substantially renewed the aesthetics of the cinematographic art of Ukraine.